The Development of an Online Learning Management System - Raduan, Wan Danish Luqman; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2022)
During the pandemic, schools were shut down, but education was converted online. With this, students and teachers both felt more burden and stress out with more workload. An Online Learning Management System was developed for La Salle Secondary School to help ease the workload for teachers while helping students have easier access to their learning material. The main objective is to develop and test a web-based system for the teachers and students in La Salle Secondary School, Kota Kinabalu to easily share materials while keeping track of their studies. The development of the system is done by using prototype methodology. This system provides seven functional modules such as login, student, teacher, administrator, to-do list, report, subject and class. Hypertext Preprocessor (PHP) is used as the main programming language while Structured Query Language (MySQL) is used to manage the database systems. This system would greatly benefit the students and teachers as it makes distributing notes easier and faster.